Identification of learning dificulties and factors causing learning difficulties in online lectures on basic biology concepts - Purbowati, Dwi; Dewi, Erlinda Rahma (Universitas Negeri Jakarta, 2024)
This study aims to identifying learning difficulties from reviewing material and factors causing learning difficulties faced by Madrasah Ibtidaiyah Teacher Education study program in online lectures basic concepts of biology. The research particiants were 80 third-semester in 2021/2022 academic year. The research method used quantitative. The data collection technique in this study is a survey technique. The research instrument is a questionnaires were made to collect student data regarding learning difficulties in basic concepts of biology and the factors that cause student learning difficulties. Questionnaires were given to students via a google form. The data analyzed by descriptive statistics and used as reference data to determine the learning difficulties faced by students in the form of subject matter, internal and external factors causing learning difficulties. The results showed: a) In online lectures on basic concepts of biology, the material that students consider the most difficult is genetics, b) Internal factors that cause learning difficulties are lack of preparation before lectures, too much memorization, lack of self-motivation, physical tiredness, and laziness to read the material, c) External factors that cause students’ learning difficulties in basic biology concepts lectures, namely lectures resources and materials, lecture facilities, lecture strategies, lecture environment, and lecture hours.